Sinergitas Mahasiswa KKN UIN Bandung Bersama Masyarakat Desa Pusakajaya Dalam Program Sosialisasi Sampah dan Jumat Bersih - Last, Ami Ratna Puri; Cindy Gysela; Muhammad Fikri Abdillah; Rifyal Zaihifni Fadli Kusyairi; Asep Shodiqin Maulana (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2023)
Field Work Lecture (KKN) activities based on the Sisdamas (Community Empowerment System) are integrative efforts aimed at strengthening the role of higher education institutions in improving the quality of life for communities through a participatory approach. One of the primary focuses of Sisdamas-based KKN is to raise community awareness of environmental issues, particularly in waste management. In this context, this abstract outlines the implementation of the "Waste Socialization and Clean Friday Program" carried out by KKN students. This program aims to enhance community awareness of the importance of sustainable waste management and contribute to environmental cleanliness. The KKN activities involve collaboration between students and the local community in the village of Pusakajaya. The "Waste Socialization Program" includes a series of activities such as workshops, seminars, and training sessions for village residents on how to segregate waste, recycle, and reduce single-use plastic waste. This is intended to change behaviors and create awareness of the negative impacts of waste on the environment. Furthermore, the "Clean Friday Program" is organized as a concrete step to periodically clean the village’s environment. This activity engages the entire village community in cleaning streets, rivers, and other public areas. It not only improves the cleanliness of the village but also strengthens solidarity and community ownership of their environment. The results achieved in this program include an increased community awareness of proper and sustainable waste management practices, a reduction in scattered waste, and increased participation in the "Clean Friday Program." These activities also illustrate the importance of a collaborative approach in addressing environmental issues. This abstract summarizes the positive contributions resulting from the "Waste Socialization and Clean Friday Program" in the context of Sisdamas-based KKN. It portrays the significance of community engagement in shaping sustainable environmental behaviors and how collaboration between students and the community can be an effective solution in promoting environmental awareness and village cleanliness.